Sex-Related Differences in Immunotherapy Outcomes of Patients with Advanced Non-Small Cell Lung Cancer - Sara Frida Cohen; Diane Cruiziat; Jeremy Naimer; Victor Cohen; Goulnar Kasymjanova; Alan Spatz; Jason Agulnik (Current Oncology)
Background: Immunotherapy with ICIs has revolutionized the treatment for NSCLC. The impact of sex on treatment outcomes remains unclear. The aim of this study was to evaluate sex-related differences in immunotherapy outcomes in a real-world population of NSCLC patients. Methods: Demographics, clinical, pathological characteristics, and treatment-related variables were analyzed to understand the differences in efficacy and safety outcomes in relation to sex. Results: 174 advanced NSCLC patients receiving first-line ICIs, either alone or in conjunction with chemotherapy, were included. No differences based on gender were observed in PFS and OS. Prognostic factors for OS and PFS included liver metastases and CRP levels at treatment discontinuation (TD). IrAE-related TD occurred at a significantly higher rate in females. GI toxicity, including hepatitis and colitis, was predominantly observed in females, whereas pneumonitis was the most frequent irAE leading to TD in males. Conclusions: Despite no significant differences based on gender being observed in survival outcomes, our study showed that female patients with advanced NSCLC receiving ICIs are at a substantially greater risk of severe symptomatic irAEs and TD. This finding indicates that broad-based sex differences could potentially exist and emphasizes the need for further investigations into the role played by gender in immunity and cancer immunotherapy treatment.